A Robust Wearable Point‐of‐Care CNT‐Based Strain Sensor for Wirelessly Monitoring Throat‐Related Illnesses. (7th May 2021) - Qaiser, Nadeem; Al‐Modaf, Fhad; Khan, Sherjeel Munsif; Shaikh, Sohail Faizan; El‐Atab, Nazek; Hussain, Muhammad Mustafa
Abstract: Point‐of‐care testing (POC) has the ability to detect chronic and infectious diseases early or at the time of occurrence and provide a state‐of‐the‐art personalized healthcare system. Recently, wearable and flexible sensors have been employed to analyze sweat, glucose, blood, and human skin conditions. However, a flexible sensing system that allows for the real‐time monitoring of throat‐related illnesses, such as salivary parotid gland swelling caused by flu and mumps, is necessary. Here, for the first time, a wearable, highly flexible, and stretchable piezoresistive sensing patch based on carbon nanotubes (CNTs) is reported, which can record muscle expansion or relaxation in real‐time, and thus act as a next‐generation POC sensor. The patch offers an excellent gauge factor for in‐plane stretching and spatial expansion with low hysteresis. The actual extent of muscle expansion is calculated and the gauge factor for applications entailing volumetric deformations is redefined. Additionally, a bluetooth‐low‐energy system that tracks muscle activity in real‐time and transmits the output signals wirelessly to a smartphone app is utilized. Numerical calculations verify that the low stress and strain lead to excellent mechanical reliability and repeatability. Finally, a dummy muscle is inflated using a pneumatic‐based actuator to demonstrate the application of the affixed wearable next‐generation POC sensor. Abstract : A point‐of‐care (POC) wearable strain sensor is developed to monitor the magnitude of swelling/relaxation of the parotid gland, which can help medical practitioners identify viral infections or throat‐related illnesses in earlier stages. The results show that the polymer‐based POC sensing patch can effectively track muscle motion with a high gauge factor and low hysteresis. The output signals of the POC sensing patch are wirelessly monitored on the phone using a Bluetooth‐low‐energy setup and a customized app.